Eliminating excessive tariffs on exports of least developed countries - Hoekman, Bernard M. 1959- (Policy research working paper, 2001)
Average most-favored-nation tariffs in the "Quad" (Canada, the European Union, Japan, and the United States) have fallen to about 5 percent. But tariffs more than three times the average most-favored-nation duty are not uncommon in the Quad and have a disproportionate effect on exports of least developed countries. Giving the poorest countries duty-free access for peak-tariff products would increase their total annual exports by roughly